Os sujeitos do trabalho mistificados pela apropriação da concepção de nova classe média: contrarreformas, perda de direitos e desafios para a classe trabalhadora - Cruz, Renatha Cândida da (2020)
Until the beginning of the 21st century, Brazil has presented different nuances of the new morphology of work. Although the work subjects profited from the increasing of formal employment in the first decade of the century, in the subsequent ten years they would distance from formal labor and social security rights and approach informality. In the Northwest Region of Goiânia, workers who presented themselves mainly in formal employment activities in 2010 Demographic Census would perform mostly informal activities in 2017. This thesis investigates which elements stimulated the worker’s approval of the expropriation of labor and social security, considering these women and men had previously expressed their wish for maintenance of their collective achievements. Therefore, we start this investigation by analyzing media and institutional discourses, which reduced to a large extent the resistance of the work subjects. Among these speeches, we highlight those related to the formation of the “new middle class”, produced in 2012 by the Secretariat of Strategic Affairs of the Presidency of the Republic (SAE/PR); which were extensively adopted by the workers, culminating in the country’s approval of the neoliberal agenda. In this sense, we seek to demonstrate that the use of income averages and consumption patterns makes it impossible to understand socio-spatial inequalities, especially when gender and race are presented. We also aim to analyze the discourses that emphasize the expropriation of constitutional rights in Brazil in the 21st century, in order to understand the precariousness of life and work, the coloniality of power and the socio-spatial inequalities. In order to do so, we investigate the changes in the world of work and the intensification of forms of control of life and work, taking as reference the workers living in the Metropolitan Region of Goiânia (RMG). In addition to deconstructing the concept of the “new middle class” from the analysis of income, we seek to present the profile, the living conditions and the precarious work of these individuals. From the perspective of geographic analysis, we finally examine the preponderance of capital in Brazil today and the manifestations of fundamental rights ensured in the Federal Constitution (such as work and social security). We do so in order to discuss the hegemonic groups, the speeches that aim the manipulation